Improving Curriculum Content of Electrical/Electronics Engineering of Polytechnics in North-East Nigeria for Technology Driven Curriculum - Vincent, Chatramada; John, Wafudu Satumari; Asukwo, Aniekan Elijah (Online Journal for TVET Practitioners, 2021)
The study was aimed at improving the curriculum content of electrical/electronics engineering of polytechnics in North-East Nigeria for a technology driven curriculum. The purpose of the study was to determine the types of microcontrollers and general content of microcontrollers relevant for inclusion into the electrical/electronics engineering curriculum of polytechnics in North-East Nigeria. The study adopted a descriptive survey research design. The population of the study was 109, which comprised 60 lecturers and 49 industry supervisors. The entire population was used for the study, hence, no sampling was employed. The instrument used for data collection was a structured questionnaire titled: Questionnaire for Improving Curriculum Content of Electrical/Electronics Engineering (QICCEEE) developed by the researchers. The instrument was validated by three experts and a reliability of 0.87 was obtained using Cronbach Alpha method. Mean and t-test were used to answer the two research questions and the null hypotheses were tested at 0.05 level of significance. Findings of the study revealed that STMicroelectronics Microcontrollers, Renesas Microcontrollers, NXP Microcontrollers, ON Semiconductor Microcontrollers, Motorola Microcontrollers, and Panasonic Microcontrollers are some of the major types of microcontroller relevant for inclusion into the electrical/electronics engineering curriculum; Seven clusters of Processor Core, Memory, Digital Input/output, Interrupts, Timer, Communication Interface, and Hardware are the general contents of microcontrollers relevant for inclusion into the electrical/electronics engineering curriculum. The study recommended among others that government should train electrical/electronics engineering lecturers of polytechnics in North-East Nigeria in the area of the newly identified curriculum contents.